Fighting misinformation in college: students learn to search and evaluate online information through flexible modules. Issue 1 (27th January 2022) - McGrew, Sarah; Chinoy, Ira
Abstract : Purpose: College students need more support learning to effectively search for and evaluate online information. Without such skills, students are vulnerable to mis- and disinformation that may appear in their search results, Web browsing and social media feeds. This study investigated four short instructional modules four short instructional modules that were developed to be delivered asynchronously to teach effective approaches to online search and evaluation. Design/methodology/approach: This exploratory study analyzed pre- and post-tests that students in two journalism courses completed before and after the modules. A total of 29 students completed written versions of the pre- and post-tests and 8 students participated in interviews in which they thought aloud while completing the pre- and post-tests. Written and oral responses were analyzed to understand students' search and evaluation strategies and how, if at all, these shifted from pre- to post-test. Findings: From pre- to post-test, students showed evidence of using strategies that were introduced in the modules to search for and evaluate online content. On the post-test, more students engaged in lateral reading to evaluate unfamiliar websites, used search operators and tools and more critically evaluated elements of the search engine results page. Originality/value: This study provides initial, positive evidence for the efficacy of embedding short, asynchronous modules in college courses to improve students' approaches to online searches and evaluations. College students need such support and modules like the ones investigated in this study may be one way to provide it.